Od prvega šolskega dne do obletnic matur - Balkovec Debevec, Marjetka (Etnolog. Nova vrsta (Ljubljana), 2014)
The activities and life in a school always reflect wider socio-political, cultural, and economic developments and conditions. The close interlinkage between all these factors has always shown in school celebrations. School festivals are an integral part of the school year and activities.The article presents school festivals, especially from the second half of the 19th century onwards, in three major groups: 1. Local festivals and important events. 2. Festivals as part of civic, patriotic, or ideological education. 3. Festivals at the beginning and end of the school year and at the completion of schooling. In the first group the author emphasizes that pupils and teachers participated in all important local events. She presents examples of celebrations of church and state holidays, welcoming important visitors, openings of new buildings, traffic, industrial, or other infrastructure. The second group of school festivals is mainly dedicated to the civic, patriotic, or ideological education carried out in schools at several levels, and most explicitly in the celebration of the personal anniversaries and various events related to the country%s ruler and his family. This is followed by examples from the period of the Habsburg monarchy and its imperial rule, that of the Kingdom of Yugoslavia and the Karadjorjević dynasty, and from the period of socialist Yugoslavia and its president Tito. The third group of school festivals includes celebrations ranging from the first school day to the anniversaries of secondary school graduation; these are largely related to the individual%s personal experiences. The beginning of the school year has always been connected with special preparations and celebrations, and equal attention has been dedicated to the end of the school year. Particularly festive events were the completion of secondary education (matura - AS and A-levels), final school excursions, (primary school) graduation balls, and secondary school graduation balls. The anniversaries of secondary school graduation function as a continuation of school celebrations. The article presents an overview of school festivals in different periods and relates them to contemporary schooling.
Keywords: ethnology; etnologija; school; šolstvo; ljudske šege; prazniki; matura; Slovenia; Slovenija; 19./20.st.